Reinforcement learning based autonomic virtual machine management in clouds - Habib, Arafat; Khan, Muhidulislam (© 2016 IEEE, 2018)
This conference paper was published in the IEEE Xplore [ © 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/ICIEV.2016.7760166 The Journal's website is at: http://ieeexplore.ieee.org/document/7760166/